Exercise-Intervened Circulating Extracellular Vesicles Alleviate Oxidative Stress in Cerebral Microvascular Endothelial Cells Under Hypertensive Plus Hypoxic Conditions - Smara Sigdel; Shuzhen Chen; Gideon Udoh; Jinju Wang (Antioxidants)
Our group has recently demonstrated that exercise intervention affects the release and function of bone marrow endothelial progenitor cell-derived extracellular vesicles (EVs) in transgenic hypertensive mice. Whether such an exercise regimen can impact circulating EVs (cEVs) remains unknown. In this study, we investigated the influence of exercise on cEV level and function. Transgenic hypertensive mice (Alb1-Ren) underwent 8-week treadmill exercise (10 m/min for 1 h, 5 days per week). Age- and sex-matched sedentary Alb1-Ren mice served as controls. cEVs were isolated from the blood of exercised and sedentary mice and are denoted as ET-cEV and nET-cEV, respectively. cEVs were labeled to determine their uptake efficiency and pathways. The functions of cEVs were assessed in an Angiotensin II (Ang II) plus hypoxia-injured cerebral microvascular endothelial cell (mBMEC) injury model. Cellular migration ability and oxidative stress were evaluated. We found that treadmill exercise stimulated cEV release, and ET-cEVs were more prone to be internalized by mBMECs. The ET-cEV internalization was mediated by macropinocytosis and endocytosis pathways. Functional studies showed that ET-cEVs can improve the compromised migration capability of mBMECs challenged by Ang II plus hypoxia. Additionally, ET-cEV treatment upregulated the expression of p-Akt/Akt in mBMECs. Compared to nET-cEVs, ET-cEVs significantly reduced ROS overproduction in Ang II plus hypoxia-injured mBMECs, associated with decreased Nox2 expression. All these findings suggest that exercise-intervened cEVs can protect cerebral microvascular endothelial cells against hypertensive and hypoxic injury.